Carbon Nanorod−MoS2 Core−Sheath Heterostructure and Its Electrochemical Properties over Various Electrochemical Windows. Issue 9 (5th March 2018) - Wu, Manman; Liu, Cong; Xu, Hui; Shen, Jiandong; Yang, Yang; Yang, Gang
Abstract: The powder of a carbon nanorod−MoS2 core−sheath heterostructure is successfully synthesized by using a hydrothermal method. The carbon nanorod−MoS2 material is composed of hierarchical MoS2 nanosheets tightly grown on carbon nanorods, in which the carbon nanorods as a template effectively reduce the aggregation of the MoS2 nanosheets. The electrochemical properties of the carbon nanorod−MoS2 composite electrode are studied in detail, as the intercalation of lithium into MoS2 includes two significant changes in lithiation mechanism, which occur over various electrochemical windows, such as from 1.0 to 3.0 V and from 0.001 to 3.0 V. The former mainly corresponds to the intercalation/extraction of lithium cations, and thus it presents excellent cyclic stability but low specific capacity. The later causes a big phase change in the final Li‐Sulfur battery system, and thus delivers a high specific capacity but is accompanied by serious pulverization and consequential fast capacity fading. MoS2 supported by carbon nanorods presents a better electrochemical performance than the pure MoS2 sample over various electrochemical windows. Abstract : Pros and cons: CNR‐MoS2 is composed of hierarchical MoS2 nanosheets tightly grown on carbon nanorods (CNRs). CNR‐MoS2 lithium intercalation includes two changes at electrochemical windows 1.0–3.0 V and 0.001–3.0 V. The former corresponds to intercalation/extraction of lithium, which presents excellent cyclic stability but low specific capacity. The latter causes a large phase change in the final Li‐S battery system, which delivers a high specific capacity but is accompanied by serious pulverization and fast capacity fading.